2013
DOI: 10.1002/we.1681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of composite fiber orientation on wind turbine blade buckling resistance

Abstract: This paper utilized the inherent directional properties of composite materials to increase the critical buckling load of a 70 m carbon/glass hybrid wind turbine blade. The effect of changing the fiber orientations of the less stiff, off-axis glass fiber plies (referred to as stability plies in this paper) was studied via nonlinear finite element buckling simulations. The orientation of the stability plies was found to influence the onset of the Brazier effect, which further influenced blade stability and buckl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…This had a negligible effect on bending stiffness and the first flap wise natural frequency. Reductions in torsional stiffness were observed for the optimal fiber orientations but were found to have negligible impacts on the flap‐wise loads and CBLs .…”
Section: The Recent Approach Toward Materials For Small Wind Turbine mentioning
confidence: 96%
See 2 more Smart Citations
“…This had a negligible effect on bending stiffness and the first flap wise natural frequency. Reductions in torsional stiffness were observed for the optimal fiber orientations but were found to have negligible impacts on the flap‐wise loads and CBLs .…”
Section: The Recent Approach Toward Materials For Small Wind Turbine mentioning
confidence: 96%
“…In addition, carbon fiber reinforced composites are used in the large scale [24,26,27,56,57]. In 2014, it was analyzed that an orientation of carbon fibers has a great effect of buckling resistance of wind turbine [58]. Even though the hybrid material structures is expensive, it has the following advantages; Since the usage of carbon fiber can be reduced by using hybrid reinforcements (E-glass/carbon, E-glass/aramid, etc.).…”
Section: Glass and Carbon Fiber Compositementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been suggested that blade buckling, especially with regard to nonlinear effects, is of concern for longer blades. ()…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been suggested that blade buckling, especially with regard to nonlinear effects, is of concern for longer blades. [3][4][5][6][7] Wind turbine blade design typically relies heavily on computationally efficient, reduced-order aerodynamic and structural models, especially in the early stages of blade design. This is a sensible approach given a vast design space, the large number of design iterations typically performed, and the ample accuracy of many reduced-order models.…”
mentioning
confidence: 99%